(untitled) (Journal of Partial Differential Equations, 2001)
This paper is concerned with the existence of solutions to the equation D_j(a^ij(x,u)D_i,u)-12D_sa^ij(x,u)D_iuD_ju + λ u = 0 on a bounded domain under the Neumann boundary condition aij(x,u)D_iuϒ_j = lul^2n-2 u.